Divine Diplomacy: Religious Influence in Global Policymaking - Wahyu, Fitri Pebriani; Fadly, Ahmad Mufarih Hasan (FISIP UIN Sunan Gunung Djati Bandung, 2023)
Research Problem: This research aims to investigate the complex interactions between religion and global policymaking and their impact on international relations. Research purposes: The aim of this research is to comprehensively investigate the influence of religion on diplomatic decisions and international relations, as well as to provide a deeper understanding of how global policy is influenced by religious beliefs. Research methods: The research methods used include analysis of historical documents, diplomatic archives, and qualitative interviews with key stakeholders such as policy makers and religious leaders. This research approach provides a nuanced exploration exploring the multi-faceted dimensions of religious influence on diplomatic decisions and international relations. Results and Discussion: This research highlights historical patterns of religious influence on foreign policy and makes significant contributions to academic discussions of international relations. The results of this research help understand the motivations and actions of states in the context of a complex geopolitical landscape. Research Implications and Contributions: The implications of this research extend to policymakers, scholars, and the general public by providing a deeper understanding of how religious beliefs shape global strategy. By recognizing this dimension in diplomatic interactions, this research provides a basis for creating culturally sensitive and effective foreign policy, promoting dialogue, and strengthening cooperation between countries with diverse religious backgrounds.